2021
DOI: 10.1172/jci139552
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylome and transcriptome landscapes of cancer-associated fibroblasts reveal a smoking-associated malignancy index

Abstract: Unlike the better-studied aberrant epigenome in the tumor, the clinicopathologic impact of DNA methylation in the tumor microenvironment (TME), especially the contribution from cancer-associated fibroblast (CAF), remains elusive. CAFs exhibit profound patient-to-patient tumorigenic heterogeneity. We ask whether such heterogeneity may be exploited to quantify the level of TME malignancy or not. We developed a robust and efficient methylome/transcriptome co-analysis system for CAFs and paired normal fibroblasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Also, other researchers have reported that DNA methylation is associated with cigarette smoking [ 34 37 ], and changing the methylation in one CpG could induce gene expression [ 38 ]. Thus, due to the involvement of CS in alteration of DNA methylation status [ 39 , 40 ], and in hampering the expression of EYA4 in lung tissues taken from smokers compared to nonsmokers [ 27 ] as well as the impact of DNA methylation in depleting EYA4 expression in oral [ 41 ] and colon cancer [ 31 ], we suggest that CS could have a role in changing the methylation status of EYA4 in Saudi population.…”
Section: Discussionmentioning
confidence: 99%
“…Also, other researchers have reported that DNA methylation is associated with cigarette smoking [ 34 37 ], and changing the methylation in one CpG could induce gene expression [ 38 ]. Thus, due to the involvement of CS in alteration of DNA methylation status [ 39 , 40 ], and in hampering the expression of EYA4 in lung tissues taken from smokers compared to nonsmokers [ 27 ] as well as the impact of DNA methylation in depleting EYA4 expression in oral [ 41 ] and colon cancer [ 31 ], we suggest that CS could have a role in changing the methylation status of EYA4 in Saudi population.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the effect of CAF heterogeneity on the "methylome", Su et al . constructed a methylation index (MIND) for NF/CAF discrimination in NSCLC (Su et al 2021 ). MIND was based on 54 smoking-associated CpG sites and was suggested to reflect the malignancy of the TME and predict patient survival.…”
Section: Tumor Fibrosismentioning
confidence: 99%
“…The mechanism contributing to the phenotypic and functional heterogeneity among fibroblasts remains an issue in the lung cancer field. Emerging data on the functional heterogeneity of CAFs in lung cancer have started to appear (Su et al 2018 , 2021 ; Hao et al 2019 ; Hu et al 2021 ). Using bulk RNA-seq TCGA data, Dominguez et al .…”
Section: Tumor Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…This similarity was in contrast to the organ-dependent transcriptomic difference of normal fibroblasts. Recently, genome-wide DNA methylation and gene expression profiling of lung CAFs and patient-matched NFs identified a methylation index of 54 CpG sites for CAF/NF discrimination [33]. Of clinical importance, this methylation index could stratify the malignant status of the tumor microenvironment among different patients and serve as a biomarker to predict recurrence in multiple lung cancer cohorts.…”
Section: Diversity and Organ Specificity Of Fibroblastsmentioning
confidence: 99%